'Actinotignum timonense' sp. nov., a new bacterial species isolated from a human urine sample. (March 2017) - Brahimi, S.; Cadoret, F.; Fournier, P.-E.; Moal, V.; Raoult, D.
Abstract: We report here the main characteristics of ' Actinotignum timonense ' strain Marseille-P2803 T (= CSUR P2803) that was isolated from the urine sample of a 59-year-old man with end-stage renal disease.